Answer:
Degree = 4
Step-by-step explanation:
The degree of a term is the sum of the exponents of its variables and the degree of a polynomial is the highest degree of all its terms. The highest degree of all the terms in −65b+53x^3y is 4. So, the degree of −65b+53x^3 y is 4.
Answer:
4
Step-by-step explanation:
The degree is the largest exponent on the variable.
4
Answer:
That is so cool
Step-by-step explanation:
Wait was that the whole question
ft2
7/9-1/4 plz help i forgot how to do dis
Answer:
19/36
Step-by-step explanation:
you find a common denominator
Answer:
19/36
Step-by-step explanation:
make the fractions have a common denominator. So you would multiply the top and bottom of 7/9 by 4. you would then get 28/36. Now multiply your other fraction by 9 top and bottom and you get 9/36. now subract the top and keep the bottom the same. and voila there is your answer
The correct answer is option B which is the graph in the figure is made up of the equation y = x² - 6x + 10.
A graph is the representation of the data on the vertical and horizontal coordinates so we can see the trend of the data.
The graph is representing the equation y = x² - 6x + 10. Since it is a parabolic equation so the graph is an inverted parabola the graph is attached below with the answer.
Thereforethe correct answer is option B which is the graph in the figure is made up of the equation y = x² - 6x + 10.
To know more about graphs follow
#SPJ2
so you for sure cross off the 1st and 3rd problem off and if you choose the last one your answer would be in th left side of the y axis so it the 2nd answer
Answer:
31
Step-by-step explanation:
Let the numbers be x and y.
"The sum of two numbers is 43." gives us the first equation.
x + y = 43
"One number is five less than three times the other number." gives us the second equation.
y = 3x - 5
Now we solve the system of two equations below.
x + y = 43
y = 3x - 5
Since the second equation is already solved for y, we will use the substitution method. We substitute 3x - 5 for y in the first equation.
x + y = 43
x + 3x - 5 = 43
4x - 5 = 43
4x = 48
x = 12
The first number is 12. Now we find the second number.
x + y = 43
12 + y = 43
y = 31
The larger number is 31.
Answer:
31 is greater
Step-by-step explanation:
I will solve your system by substitution.
x=3y−5;43=x+y
Step: Solve x=3y−5 for x:
Step: Substitute 3y−5for x in 43=x+y:
43=x+y
43=3y−5+y
43=4y−5 (Simplify both sides of the equation)
43+−4y=4y−5+−4y (Add -4y to both sides)
−4y+43=−5
−4y+43+−43=−5+−43 (Add -43 to both sides)
−4y=−48
(Divide both sides by -4)
y=12
Step: Substitute12foryinx=3y−5:
x=3y−5
x=(3)(12)−5
x=31(Simplify both sides of the equation)
Answer:
x=31 and y=12
31 is greater than 12